Chemical characterization, evaluation of the antibacterial and antioxidant activities of the essential oil of Algerian (Myrtus communis L). - Benhadid, Rym; Hadef, Youcef; Djahoudi, Abdelghani; Hosni, Karim (Progress in Nutrition, 2022)
The essential oil extracted from Algerian Myrtle were analysed by gas chromatography/mass spectrometry (GC/MS),  it revealed 62 components accounting for 98.62 % of the oil. The major components were α-pinene (24.83 %), 1,8-cineole (10.8 %), limonene (6.07 %), α-Terpineol (4.14%). Methyl eugenol (3.48%), The in vitro antibacterial activity was performed by agar disc diffusion and (MIC). The oil was tested against Staphylococcus aureus, Staphylococcus aureus ATCC 29213, Staphylococcus aureus ATCC 25923, Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli ATCC  25922, ciprofloxacin resistant Escherichia coli (E. coli cip R). Pseudomonas aeruginosa VIM 2, imipenem- resistant Pseudomonas aéruginosa (Pseudomonas aeruginosa IMP), Pseudomonas aéruginosa ATCC 27853, Enterobacter cloacea, carbapenemase-negative Klebsiella pneumonia (KPC -), carbapenemase-positive Klebsiella pneumoniae (KPC+), Klebsiella pneumoniae, Acenitobacter baumannii. The antibacterial test revealed that myrtle oil showed a good antibacterial effect except against pseudomonas. The antioxidant activity of essential oil was evaluated by DPPH assay. The results showed the highest free radical scavenging activity with dpph (93.39 %) at the concentration of EO 4 mg/ml.